Training-Dependent Change in Content of Association in Appetitive Pavlovian Conditioning - Kim, Hea-jin; Koh, Hae-Young (Frontiers in Behavioral Neuroscience, 2021)
In appetitive Pavlovian conditioning, experience with a conditional relationship between a cue (conditioned stimulus, CS) and a reward (unconditioned stimulus, US) bestows CS with the ability to promote adaptive behavior patterns. Different features of US (e.g. identity-specific sensory, general motivational) can be encoded by CS based on the nature of CS-US relationship experienced (e.g. temporal factors such as training amount), and the content of association may determine CS’s influence over behavior (e.g. mediated learning, conditioned reinforcement). The content of association changed with varying conditioning factors, thereby altering behavioral consequences, however, has never been addressed in relevant brain signals evoked by CS. Our previous study found that PLCβ1-KO mice display persistent mediated learning over the extended course of odor-sugar conditioning, and that wild-type (WT) mice lose mediated learning sensitivity after extended training. In the present study, in order to see whether this behavioral difference between these two genotypes comes from a difference in the course of association content, we examined whether odor CS can evoke the taste sensory representation of an absent sugar US after minimal- and extended training in these mice. In contrast to WT which lost CS-evoked neural activation (c-Fos expression) in the gustatory cortex after extended training, KO mice displayed persistent association with the sensory feature of sugar, suggesting that sensory encoding is reliably linked to mediated learning sensitivity, and that there is a training-dependent change in the content of association in WT. PLCβ1 knockdown in the left mPFC resulted in mediated learning sensitivity and CS-evoked gustatory cortical activation after extended training, proposing a molecular component of the neural system underlying this Pavlovian conditioning process. We also discuss how disruption of this process is implicated for hallucination-like behaviors (impaired reality testing).